Pengaruh Metode Biblioterapi terhadap Pengetahuan Remaja tentang Hygiene Menstruasi di SMP Negeri 2 Mayang Kabupaten Jember (The Effect of Bibliotherapy Method toward knowledge of Adolescents at SMP Negeri 2 Mayang Jember District) - Irma Yanti Hidayah; Ratna Sari Hardiani; Mulia Hakam (Pustaka Kesehatan, 2016)
Adolescent is one of the period human development that is very important. In this case so many instances life and change that will matter with a teenager will determine the quality of life in adulthood. Reproductive health problems happened in adolescents largely caused by infection that can happen because a lack of maintenance adolescent to instrument reproduction. Hygiene menstruation is the hygiene individuals with a crucial role in behavior health a woman hygiene a particularly when menstrual reproduction. The purpose of this research is analyst influence method of bibliotherapy toward knowledge of adolescents about hygiene menstruation at SMP Negeri 2 Mayang Districts of Jember. Design used is quasi experimental with nonequivalent control group design. The sampling method used is cluster sampling with sample students as many as thirty students. The analyzed used Mann Whitney. Pre test results showed 76,7% sufficient knowledge at twenty three students and 3,4 % (one students) good knowledge. The post test on fifteen students intervention’s group 80% (twelve students) good knowledge and 20% (three students) sufficient knowledge, while in the control group because not given method bibliotherapy 100 % sufficient knowledge. The researcher suggest the school to do bibliotherapy method to increase knowledge about hygiene menstruation students. Keywords: bibliotherapy, hygiene menstruation, adolescent